Sistem Pakar Diagnosa Penyakit Gigi dan Mulut Menggunakan Metode Certainty Factor - Bayu Adji Sukarno; Anief Fauzan Rozi (Universitas Mercu Buana Yogyakarta, 2021)
Teeth are one of the most important organs in the human body. As an organ that cannot heal itself, teeth need to be carefully taken care of. The data on dental health in Indonesia obtained from the Center for Data and Information (Pusdatin) of the Ministry of Health, Republic of Indonesia Year 2014 revealed that the percentage of Indonesians with dental health problems in 2007 and 2013 increased from 23.2% to 25.9%. The population receiving dental medical care increased from 29.7% in 2007 to 31.1% in 2013. People need a quick response to get their teeth checked before going to a dentist whose location might be far from their home. An early response to handle a dental disease that someone may suffer is essential. Therefore, a quick way to diagnose a dental disease that can be done by everybody is needed. This research is to develop an expert system to diagnose dental and oral diseases. This system is to assist people with an early diagnosis so that a more severe disease can be prevented.